Sesame Street mecha builders. The complete series [videorecording (DVD)] - Fallon, Joe (Shout! Kids, 2024)
Mecha Elmo, Mecha Cookie Monster, and Mecha Abby are ready to problem-solve the most out-of-this-world situations. Using their robo skills, the Mecha Builders are here to help it just might take them a few tries before they save the day!